The Effect of Emotic Health Education On Parents' Knowledge of Early Detection of Emotional Mental Health In Preschool Children In Kandangmas Village - Dwi Della Puspita; Indanah Indanah; Sri Karyati (International Journal of Health and Pharmaceutical (IJHP), 2025)
One of the most common problems in preschoolers is emotional mental health issues. Emotional mental health disorders are a condition that indicates an individual is experiencing an emotional change that can develop into a pathological state if it continues. Therefore, to prevent the occurrence of more severe mental and emotional problems in preschoolers, early detection of emotional mental health is needed. The delivery of health education is more interesting by using animated videos is one of the effective methods because respondents can see and listen directly, so that information is easier to understand and remember. The results of this research can be the basis for development (penkes) through animated videos and encourage the public to increase education about early detection of emotional mental health in preschoolers. In the long term, this research is expected to increase parental awareness in recognizing the signs of children's mental-emotional disorders and disseminate effective information dissemination and build positive behavioral changes in parenting. This study aims to determine the influence of "emotic" health education on parents' knowledge about early detection of emotional mental health in preschool children in Kandangmas Village, Dawe District, Kudus Regency. This study used a quasi-experimental method with a pre-test post-test control group design, which compared the differences before and after intervention in the intervention and control groups. The study respondents amounted to 50 parents who had preschool-age children, who were selected based on the inclusion criteria and the exclusion criteria that were determined to be willing to be respondents.